2022
DOI: 10.1111/cts.13382
|View full text |Cite
|
Sign up to set email alerts
|

Association between betamethasone levels and respiratory distress syndrome in preterm births: A prospective cohort study

Abstract: The recommended fixed dosage of betamethasone for pregnancies at risk of preterm birth was determined in the 1970s, regardless of gestational age (GA), number of fetuses, and maternal weight. We aimed to examine the association between maternal and neonatal betamethasone serum levels and neonatal respiratory distress syndrome (RDS) and to examine whether levels correlate with maternal weight, GA, or number of fetuses. A prospective study was conducted at a single academic medical center between August 2016 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Petersen et al 32 reported C f p ∕ C m p = 0.28 for BET with no time dependence and the first observation recorded at 1 h after the last dose. Similar findings for BET with C f p ∕ C m p = 0.37were reported by Ballard et al 33 A recent study by Zafran et al 34 in women dosed with BET-PA reports the value of C f p ∕ C m p = 0.72 for BET calculated as the ratio of mean values. The twofold difference from previous values might be explained by a relatively large between-subject variability of C f p and C m p in their study.…”
Section: Discussionsupporting
confidence: 83%
“…Petersen et al 32 reported C f p ∕ C m p = 0.28 for BET with no time dependence and the first observation recorded at 1 h after the last dose. Similar findings for BET with C f p ∕ C m p = 0.37were reported by Ballard et al 33 A recent study by Zafran et al 34 in women dosed with BET-PA reports the value of C f p ∕ C m p = 0.72 for BET calculated as the ratio of mean values. The twofold difference from previous values might be explained by a relatively large between-subject variability of C f p and C m p in their study.…”
Section: Discussionsupporting
confidence: 83%